All-optical Switches based-on GaAs/AlAs Quantum Dots Vertical Cavities - C. Teeka; R. Jomtarak; P.P. Yupapin (My University, 2012)
Abstract In this paper, we present an all-optical switch based on self-assembled GaAs/AlAs quantum dots (QDs) within a vertical cavity. Two essential aspects of this novel device have been investigated, which includes the QD/cavity nonlinearity with appropriately designed mirrors and the intersubband carrier dynamics inside QDs. Verticalreflection- type switches have been investigated with an asymmetric cavity that consists of 12 periods of GaAs/Al0 . 8Ga0 . 2As for the front mirror and 25 periods for the back mirror. The thicknesses of the GaAs and AlGaAs layers are chosen to be 89 and 102 nm, respectively. To give a dot-in-a-well (DWELL) structure, 65 nm dimension of Si was deposited within an 20 nm AlAs QW. All-optical switching via the QD excited states has been achieved with a time constant down to 750 fs, wavelength tunability over 29.5 nm. These results demonstrate that QDs within a vertical cavity have great advantages to realize low-power consumption polarization-insensitive micrometer-sized switching devices for the future optical communication and signal processing systems
Keywords: Semiconductor Quantum Structures and Devices